CONTESTATIONS BETWEEN MINIMARKET RETAIL AND LOCAL GROCERY STORES IN ACEH, INDONESIA - Faizul Aulia; M Nazaruddin; Alwi Alwi (JURNAL ILMU SOSIAL, 2024)
This article examines the competition between minimarket retailers and local grocery stores from a sociological perspective. It explores two main patterns of daily shopping habits, which highlight a complex competition for consumer attention. The author aims to demonstrate that this contestation is linked to social change and the business strategies employed by each type of business. The study adopts a descriptive qualitative approach, conducted in Lhokseumawe City, Aceh Province, Indonesia. Data were gathered through observation, in-depth interviews, and literature review, and analyzed descriptively by reducing, verifying, and interpreting to identify key themes and insights. The findings show that the competition between these two shopping patterns is driven by changes in consumer behavior. Minimarkets succeed by offering convenience and more structured services, while local grocery stores remain competitive by providing services rooted in cultural values and fostering close community ties.